Evaluation of the RYR1 gene genetic diversity in the Latvian White pig breed - Dokāne, K.; Jonkus, D.; Sjakste, T. (Вiopolymers and Cell, 2016)
The ryanodine receptor 1 (RYR1) is a calcium ion channel in the sarcoplasmic reticulum of skeletal muscle. Multiple polymorphic loci have been identified in the RYR1 gene in human and animals and some of them are associated with certain phenotypes. However, there are still few data on the RYR1 genetic variability in pig and only the missense mutation Arg615Cys, associated with the malignant hyperthermia, porcine stress syndrome and meat quality, has been studied in several commercial and local breeds. Aim. To genotype the rs344435545 (C1972T, Arg615Cys), rs196953058 (T8434C, Phe2769Leu) and rs323041392 (G12484A, Asp4119Asn) in the Latvian local pig breed Latvian White and to evaluate the eventual functionality of amino acid substitutions. Methods. Loci were genotyped by the restriction fragment length polymorphism technology in the collection of 8 samples of original Latvian White collected in 2006 and 103 samples of Latvian White collected in three Latvian geographically distant private farms in 2015. SIFT online tool was applied to evaluate a potential effect of the amino acid substitutions on protein functions. Results. The loci rs344435545 and rs196953058 were found to be monomorphic in both collections. On the contrary, the rs323041392 showed a high level of polymorphism in the original Latvian White with GG/GA/AA genotype correlation equal to 3/4/1 and the absence of polymorphism in 2015 collection. From the studied loci, only the rs344435545 was identified as possessing the potential to change functions of the protein. Conclusions. The unfavourable rs344435545 T allele having functional effect on the protein function, appears not to have been introduced in the Latvian White pig breed. A compete loss of the rs323041392 variability in Latvian White happened in nine years of private farming;this could be a message to Latvian and other European livestock industry that the breeding intensification may decrease the genetic diversity, specific features performance and adaptability to the environmental challenges in local breeds of small populations.